2017
DOI: 10.1097/md.0000000000007940
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extracorporeal shock-wave therapy for treating patients with chronic rotator cuff tendonitis

Abstract: Background:This study aimed to determine the efficacy and safety of extracorporeal shock-wave therapy (ESWT) for treating patients with chronic rotator cuff tendonitis (CRCT).Methods:In this study, 84 patients with CRCT were randomly divided into intervention and control groups in a ratio of 1:1. Patients in the intervention group received ESWT, whereas those in the control group received placebo. The primary outcome was measured by Numeric Rating Scale (NRS). The secondary outcomes were measured by the Consta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 22 publications
1
31
0
2
Order By: Relevance
“…Th e assessment of search results evidenced a signifi cant amount of eligible studies, but also a variation in application methodology and number of sessions. Th e role of ESWT in treatment of chronic calcifying tendinitis of the rotator cuff has been evaluated in many studies [21][22][23][24][25][26][27] . Calcifying tendinitis is a frequent condition in orthopaedic and rehabilitation practice and represents a well documented cause for shoulder pain.…”
Section: Resultsmentioning
confidence: 99%
“…Th e assessment of search results evidenced a signifi cant amount of eligible studies, but also a variation in application methodology and number of sessions. Th e role of ESWT in treatment of chronic calcifying tendinitis of the rotator cuff has been evaluated in many studies [21][22][23][24][25][26][27] . Calcifying tendinitis is a frequent condition in orthopaedic and rehabilitation practice and represents a well documented cause for shoulder pain.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the treatment of non-calcific tendinopathy of the rotator cuff, the evidence supporting the ESWT treatment in short-and long-term is controversial. Li et al [31] found that, considering a total of 84 patients, pain symptomatology was improved in the high dose ESWT group. Galasso et al [32] detected a remarkable short-term efficacy in functional recovery in ESWT patients relative to a placebo group.…”
Section: Non-calcific Tendinopathy Of the Rotator Cuff (Ntrc)mentioning
confidence: 98%
“…All of the articles [11,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] included in the study focus on calcific tendinopathy of the shoulder, non-calcific tendinopathy of the shoulder, and subacromial impingement syndrome (SAIS).…”
Section: Shouldermentioning
confidence: 99%
“…Both groups had improvements over 6 months, with investigators concluding that placebo benefits were seen in the use of ESWT for this condition [10]. Li et al [71] conducted a randomized, double‐blind, placebo‐controlled trial examining patients with chronic rotator cuff tendinitis without calcifications with symptoms for greater than 6 months. The intervention was 3000 pulses of radial shockwave and EFD of 0.11 mJ/mm 2 .…”
Section: Upper Extremity Pathologymentioning
confidence: 99%
“…Five total treatments were provided with each separated by 3 days. The outcomes were measured at 4 and 8 weeks after treatment, at which time all measures, pain by numeric rating scale, Constant‐Murley Score (CMS), and Simple Shoulder Test, were significantly improved in the ESWT group over the control group [71]. Galasso et al [72] performed a double‐blind, randomized, placebo‐controlled study on 20 patients with noncalcifying supraspinatus tendinopathy and found significantly improved CMS and ROM in the ESWT group as compared to the placebo group.…”
Section: Upper Extremity Pathologymentioning
confidence: 99%